Antifungal-Loaded Acrylic Bone Cement in the Treatment of Periprosthetic Hip and Knee Joint Infections: A Review - Konstantinos Anagnostakos; Sören L. Becker; Ismail Sahan (MDPI AG, 2022)
Little is known about the clinical use of antifungal-loaded acrylic bone cement in the treatment of periprosthetic hip and knee joint infections (PJIs). Hence, we performed a literature search using PubMed/MEDLINE from inception until December 2021. Search terms were "cement" in combination with 13 antifungal agents. A total of 10 published reports were identified, which described 11 patients and 12 joints in which antifungal-loaded cement was employed. All studies were case reports or case series, and no randomized controlled trials were identified. In 6 of 11 patients, predisposing comorbidities regarding the emergence of a fungal PJI were present. The majority of the studies reported on infections caused by Candida species. In six cases (seven joints), the cement was solely impregnated with an antifungal, but no antibiotic agent (amphotericin B, voriconazole, and fluconazole). In the other five joints, the cement was impregnated with both antibiotic(s) and antifungals. Great discrepancies were seen regarding the exact loading dose. Four studies investigated the local elution of antifungal agents in the early postoperative period and observed a local release of antifungals in vivo. We conclude that there is a paucity of data pertaining to the clinical use of antifungal-loaded bone cement, and no studies have assessed the clinical efficacy of such procedures. Future studies are urgently required to evaluate this use of antifungals in PJI.